INCREASING THE SALES PRODUCTIVITY OF 'TETTE CHIPS' DURING THE TIME OF THE COVID-19 PANDEMIC, THROUGH DIGITAL MARKETING: Case study of Blumbungan Village, Larangan Pamekasan District - Fawaid, Akhmad (Jurnal Ekonomi, Bisnis & Entrepreneurship (e-Journal), 2022)
The Covid-19 pandemic that hit the world and Indonesia impacted the decline in the income of the "tette chips" sellers in Blumbungan Village, Larangan District, Pamekasan. Conventional marketing that "tette chips" sellers carry out by selling directly in traditional markets and peddling to residents' homes is impossible during the pandemic. This research aims to solve the problem faced by the "tette chips" seller by changing the sales pattern with digital marketing. The research method used in this research is the descriptive qualitative method. This research provides benefits and convenience in doing business digitally to the public, even though they were in the covid-19 pandemic period, and increased understanding of sellers about the existence of the internet. The results of this study, namely the increasing selling power of "tette chips" with digital marketing.